2016
DOI: 10.5296/jfs.v5i1.8847
|View full text |Cite
|
Sign up to set email alerts
|

Rye Bread Fortified With Cellulose and Its Acceptance by Elderlies in Nursing Homes and Young Adults

Abstract: <p>Several clinical studies suggest that a sufficient daily intake of fibres has positive effects on prevention of different diseases. Other studies show that most elderlies ingest too less fibres daily. As bread is one of the daily consumed food by elderly a brown rye bread fortified with three different cellulose fibres length (18 µm, 300 µm, 700 µm) was developed. To find out whether elderly would consume such cellulose fortified rye breads, preference tests and a questionnaire about fibres and liking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Similar observations were found by Ognean et al. (2006) and Fuckerer et al. (2016) in breads with two kinds of sodium carboxyl-methyl-cellulose and cellulose fibers with different fiber length.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar observations were found by Ognean et al. (2006) and Fuckerer et al. (2016) in breads with two kinds of sodium carboxyl-methyl-cellulose and cellulose fibers with different fiber length.…”
Section: Resultssupporting
confidence: 90%
“…Several studies have reported the potential use of cellulose fibers in bakery industry (Fuckerer et al., 2015, 2016; Poran et al., 2008; Seguchi et al., 2007; Tabara et al., 2012). Fuckerer et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to counteract the undesirable effect of C on dough characteristics and bread volume reduction, additives may be necessary, such as vital gluten or oxidizing and emulsifying agents, for development of the three‐dimensional structure (Gómez et al, 2003; Ragaee et al, 2011). Some studies have analyzed the effect of inclusion of microcrystalline C in bread and found that it had no significant impact on water absorption (Fuckerer et al, 2015; Majzoobi et al, 2007; Ozyurt & Ötles, 2016). Furthermore, the authors reported increased volume and decreased hardness of the final product.…”
Section: Chemistry Rheology and Food Application Of Fibers In Bakery ...mentioning
confidence: 99%
“…Unlike BG mentioned previously, C seems to have a greater impact on the sensory characteristics; however, the product remains well tolerated (Gómez et al, 2003). Furthermore, a positive perception was formed among elderly people when they were informed that they are consuming a DF source product (Fuckerer et al, 2016).…”
Section: Chemistry Rheology and Food Application Of Fibers In Bakery ...mentioning
confidence: 99%